High‐resolution mapping of 33 years of material stock and population growth in Germany using Earth Observation data. (25th October 2022) - Schug, Franz; Frantz, David; Wiedenhofer, Dominik; Haberl, Helmut; Virág, Doris; van der Linden, Sebastian; Hostert, Patrick
Abstract: Global societal material stock in buildings and infrastructure have accumulated rapidly within the last decades, along with population growth. Recently, an approach for nation‐wide mapping of material stock at 10 m spatial resolution, using freely available and globally consistent Earth Observation (EO) imagery, has been introduced as an alternative to cost‐intensive cadastral data or broad‐scale but thematically limited nighttime light‐based mapping. This study assessed the potential of EO data archives to create spatially explicit time series data of material stock dynamics and their relation to population in Germany, at a spatial resolution of 30 m. We used Landsat imagery with a change‐aftereffect‐trend analysis to derive yearly masks of land surface change from 1985 onward. Those served as an input to an annual reverse calculation of six material stock types and building volume‐based annual gridded population, based on maps for 2018. Material stocks and population in Germany grew by 13% and 4%, respectively, showing highly variable spatial patterns. We found a minimum building stock of ca. 180 t/cap across all municipalities and growth processes characterized by sprawl. A rapid growth of stocks per capita occurred in East Germany after the reunification in 1990, with increased building activity but population decline. Possible over‐ or underestimations of stock growth cannot be ruled out due to methodological assumptions, requiring further research.